PENGARUH 5 PESAN KELUARGA SADAR GIZI (KADARZI) TERHADAP PENGETAHUAN SIKAP DAN PRAKTEK KADARZI DI KECAMATAN MAESAAN KABUPATEN MINAHASA SELATAN - Joice Mermy Laoh (POLTEKKES KEMENKES MANADO, 2012)
In general, families have a basic knowledge of nutrition. However, attitudes and skills, andwillingness to act in improving family nutrition is low. Health Research Association(Riskesdas) 2007 national prevalence toddler malnutrition in 5.4% and 13.0% less nutrition.National prevalence nutrition more In toddlers 4.3%. Prevalence of Childhood Education Fat(Women) in North Sulawesi (8%) above the national prevalence (6.4%). Obesity prevalenceIn General Population Age ≥ 15 Years in North Sulawesi in Indonesia notch anotherprevalence (33.2%). The mean energy consumption per capita per day of North Sulawesi isbelow the national average of 1381.3 kcal (1735.5 kcal). Currently, only about 45.4% ofchildren under five were taken to the IHC for the last 6 months interval weighed as earlydetection of growth disorders. Health services that include preventive and promotive servicesindispensable in realizing KADARZI. This study aimed to determine the effect of 5 messagesnutrition-conscious families (KADARZI) for the creation of self-conscious family nutrition.This research method is a quasi-experiment Non-Equivalent Control Group Design With PreTest and Post Test, Samples is the mother of a toddler, were aged ≥ 20 years. Research sitein the District Maesaan of South Minahasa regency. Measuring tool is a questionnaire todetermine their knowledge, attitudes and practice behaviors KADARZI data analysis usingstatistical test t-test at α 0.05. Other research results are the effect of nutrition consciousfamily 5 messages on knowledge, attitudes and practices KADARZI. Through the medium ofthe book KADARZI can improve knowledge, attitude and practice of family self-consciousnutrition. Suggestion that the local government distribute 5 messages KADARZI behavior tothe public by using the book to be easily understood and practiced.